The split hand in amyotrophic lateral sclerosis: a possible role for the neuromuscular junction. Issue 5 (3rd July 2019) - de Carvalho, Mamede; Swash, Michael
Abstract: Objective: We investigated the neuromuscular junction as a possible factor leading to the split-hand phenomenon in amyotrophic lateral sclerosis (ALS). Methods: Thenar and hypothenar muscles were studied in 91 healthy control subjects and 39 ALS patients matched for age and gender. We investigated neuromuscular transmission using repetitive nerve stimulation (RNS) at 2 Hz in ulnar and median nerves in the right hand, recording from abductor pollicis brevis (APB), first dorsal interosseous (FDI), and abductor digiti minimi (ADM) muscles. In the ALS patients, these muscles were clinically and electrophysiologically normal, without neurogenic change. Sixteen ALS patients were re-studied 6 months later. The CMAP amplitude and area percent decrement in RNS was analyzed in each muscle. Results: In controls, the decrement to RNS was significantly greater in APB > FDI > ADM ( p < 0.001). In older subjects, the CMAP amplitude decreased with age, but the decrement was increased only in ADM. At the baseline study the CMAP amplitude was similar in all three muscles in control and ALS patients. In the ALS patients, the decrement during RNS was greater in APB ( p = 0.014) and FDI ( p < 0.001) than in controls, but there was no difference for ADM (0.68). In the 16 ALS patients, reevaluated 6 months later CMAP amplitude and area percent decrement changed significantly in all three muscles, but the reduction in CMAP amplitude was much greater in APB and FDI than in ADM. Conclusions: These physiological differences in distal motor nerve function in normal small hand muscles may influence vulnerability to neurogenic change in ALS. These findings support a role for a peripheral factor in the split-hand phenomenon.